Al-Qur’an dan Perubahan Sosial: Menggerakan Budaya Literasi untuk Kesejahteraan - Kris Nandang (Journal of Religion and Social Transformation, 2023)
The literacy level in Indonesia shows worrying data, quoted from UNESCO, the level of reading interest in Indonesia is only 0.001%. In other words, out of a thousand Indonesians, only one person is active in reading. This article aims to explore the Al-Qur'an and other sources related to literacy and their relevance to welfare. Considering the low level of literacy in Indonesia, joint efforts are needed to improve this condition. This research uses a qualitative method based on library research by elaborating on verses, hadith and other sources related to literacy and sources related to implementation of welfare through the theory of social change. The results of this research show that there is a connection between improving the quality of literacy and the prosperity that the whole community aspires to. Several efforts are offered in the form of grounding the urgency of literacy supported by holistic support from all parties, namely educational institutions, families and the environment as part of social change.